2021
DOI: 10.3390/nu14010107
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin as a Novel Mitochondrial Regulator: A New Aspect of Carotenoids, beyond Antioxidants

Abstract: Astaxanthin is a member of the carotenoid family that is found abundantly in marine organisms, and has been gaining attention in recent years due to its varied biological/physiological activities. It has been reported that astaxanthin functions both as a pigment, and as an antioxidant with superior free radical quenching capacity. We recently reported that astaxanthin modulated mitochondrial functions by a novel mechanism independent of its antioxidant function. In this paper, we review astaxanthin’s well-know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 235 publications
(283 reference statements)
0
36
0
Order By: Relevance
“…Similarly, astaxanthin can improve mitochondrial function in a reduced state under oxidative stress (Wolf et al, 2010). Some evidence indicates that astaxanthin contributes to mitochondrial quality control and promotes mitochondrial biogenesis through the AMP-activated protein kinase (AMPK) pathway, however, the underlying mechanism remains unclear (Nishida et al, 2020;Nishida et al, 2021).…”
Section: Mechanisms By Which Astaxanthin Defends Against Oxidative St...mentioning
confidence: 99%
“…Similarly, astaxanthin can improve mitochondrial function in a reduced state under oxidative stress (Wolf et al, 2010). Some evidence indicates that astaxanthin contributes to mitochondrial quality control and promotes mitochondrial biogenesis through the AMP-activated protein kinase (AMPK) pathway, however, the underlying mechanism remains unclear (Nishida et al, 2020;Nishida et al, 2021).…”
Section: Mechanisms By Which Astaxanthin Defends Against Oxidative St...mentioning
confidence: 99%
“…According to our research, cells treated with astaxanthin showed increased mitochondrial dynamics and biogenesis, as demonstrated by restoring mitochondrial transmembrane potential, restoring proper mitochondrial morphology, and regulating fission events and fusion dynamics. Research of Nishid et al also confirmed the beneficial effect of astaxanthin on the maintenance and enhancement of mitochondrial activity through a direct impact on the AMPK/Sirtuin/PGC-1α pathway and other pathways [ 56 ]. Nawaz et al confirmed the ability of astaxanthin to stimulate mitochondrial function, where astaxanthin was shown to reduce insulin resistance in diet or myotubule-induced obesity in vitro by modulating insulin signaling in an antioxidant and antioxidant-independent manner and by activating mitochondrial energy metabolism via the activation of the AMP-activated protein kinase pathway (AMP) coactivator γ coactivator-1 α (PGC-1 α ) peroxisome proliferator activated receptor in skeletal muscle [ 56 ].…”
Section: Discussionmentioning
confidence: 97%
“…Research of Nishid et al also confirmed the beneficial effect of astaxanthin on the maintenance and enhancement of mitochondrial activity through a direct impact on the AMPK/Sirtuin/PGC-1α pathway and other pathways [ 56 ]. Nawaz et al confirmed the ability of astaxanthin to stimulate mitochondrial function, where astaxanthin was shown to reduce insulin resistance in diet or myotubule-induced obesity in vitro by modulating insulin signaling in an antioxidant and antioxidant-independent manner and by activating mitochondrial energy metabolism via the activation of the AMP-activated protein kinase pathway (AMP) coactivator γ coactivator-1 α (PGC-1 α ) peroxisome proliferator activated receptor in skeletal muscle [ 56 ]. Yu et al proved that astaxanthin maintained mitochondrial integrity by increasing PGC-1α expression and maintained normal tubular structure and heat-induced oxidative stress in C2C12 myoblasts [ 78 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[ 29 ] Astaxanthin also has a beneficial effect on mitochondrial quality control through AMPK activation. [ 30 ] Furthermore, a recent report showed that remdesivir could induce mitochondrial fragmentation and suppress mitochondrial respiration. [ 25a ] These studies suggest that astaxanthin may exert the protective effect via acting directly on mitochondrial, which deserves further investigation in the follow‐up studies.…”
Section: Discussionmentioning
confidence: 99%